Talent Management Through Competency Tests to Improve the Quality of State Civil Apparatus - Muttaqin, Muttaqin; Rizal, A.; Asmarianti, Asmarianti (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study analyzes the implementation of talent management through competency testing as a strategy to improve the quality of the State Civil Apparatus (ASN) within the Makassar City Government. Using a qualitative case study approach, the research explores the competency gaps identified among supervisory-level employees who participated in the 2024 competency assessment conducted by BKPSDM Makassar City. Data were collected through observations (12 February–15 March 2024), documentation review, and interviews with key stakeholders. The findings show that although 93% of employees fall within the “optimal” competency mapping category, only 20% meet the requirements for higher job placements, while 40% are still developing, and another 40% fall below required standards. Significant competency gaps were found in self-development, managing change, and orientation to results. These gaps indicate that competency test results have not been fully integrated into a comprehensive talent management system, particularly in linking assessment outcomes with strategic development, placement, and career acceleration policies. The study concludes that while competency testing provides a strong diagnostic foundation, its effectiveness in strengthening talent management relies on consistent follow-up mechanisms, data-driven decision-making, and sustainable development programs. Recommendations include enhancing HR analytics, reinforcing merit-based policies, and establishing continuous monitoring to develop a professional, accountable, and high-performing ASN workforce.